2016
DOI: 10.1080/0284186x.2016.1223881
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for predicting recurrence in stage II colorectal cancer

Abstract: Our nomogram can be a useful tool for accurate prediction of recurrence in stage II colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 25 publications
1
31
0
2
Order By: Relevance
“…Half of the patients with rectal cancer had received preoperative radiotherapy, which could have resulted in eradication of lymph node metastases, and, therefore, affecting these results. A poorer prognosis for right-sided than left-sided colon cancer has been shown in stage IV CRC [25], but in stage I-III disease conflicting results are reported [26][27][28]. Right-sided colon cancer has been associated with poor differentiation grade and T4 stage, but is less likely to be node-positive, than left-sided colon cancer [27].…”
Section: Discussionmentioning
confidence: 89%
“…Half of the patients with rectal cancer had received preoperative radiotherapy, which could have resulted in eradication of lymph node metastases, and, therefore, affecting these results. A poorer prognosis for right-sided than left-sided colon cancer has been shown in stage IV CRC [25], but in stage I-III disease conflicting results are reported [26][27][28]. Right-sided colon cancer has been associated with poor differentiation grade and T4 stage, but is less likely to be node-positive, than left-sided colon cancer [27].…”
Section: Discussionmentioning
confidence: 89%
“…In a preceding issue of Acta Oncologica, Hoshino et al [7] similarly found the pronounced influence of infiltration depth. Their study created a nomogram to predict the probability of recurrence in stage II CRC, not separating colon and rectal cancer.…”
mentioning
confidence: 85%
“…Besides the three articles about radiation therapy in rectal cancer discussed above [22,42,43], another five articles in this issue of Acta Oncologica also deal with colorectal cancer [49][50][51][52][53]. Four of them concern the prognosis of early stage colorectal cancer, also a very important topic where great uncertainties about which patients should be given adjuvant chemotherapy exist.…”
Section: Modifying the Time Interval To Surgerymentioning
confidence: 99%